(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2014)
In the following article, atmospheres are discussed as media of ‘bodily felt communication’ (Hermann Schmitz). The elements, which belong to an impressive atmosphere, take effect holistically in a ‘chord’ (Willy Helpach). While differentiating according to the degree of subjective affectation, one has to distinguish between atmospheres and moods, although both have a situational character. Atmospheres are staged as powerful media of suggestion for the purpose of manipulative communication. Therefore, the re-alphabetization of the perception of emotions and the ability to communicate about them eventually offer a higher degree of self-determination. Michel Foucault’s ‘hermeneutics of the subject’ will be harnessed theoretically for the differentiation of an affective self-control.